Effect of ytterbium co-doping on erbium clustering in silica-doped glass. (9th January 2015) - Kiritchenko, N V; Kotov, L V; Melkumov, M A; Likhachev, M E; Bubnov, M M; Yashkov, M V; Laptev, A Yu; Guryanov, A N
Abstract: The effect of ytterbium co-doping on erbium ion clustering in silica-based glass was studied. It was experimentally shown that the pump-to-signal conversion efficiency could be significantly increased if the number of Yb 3+ ions in the fiber core was 20 times higher than the number of Er 3+ ions. Estimations of the number of Er 3+ ions in clusters confirmed a decrease in their clustering at high Yb concentrations.